PENGARUH HAMBATAN SAMPAI TERHADAP KARAKTERISTIK LALU LINTAS PADA RUAS JALAN RTA MILONO KM 9 KOTA PALANGKA RAYA - Miming Virganinda; Henriko Pasaribu (Huma Tabalien Jurnal (HTJ) Teknik Sipil, 2022)
The highway is a land transportation infrastructure that plays a very important role very important in the transportation sector, especially for the continuity of distribution goods and services. The condition of the road that is often traversed often causes dense currents traffic so that it can cause vulnerabilities in the form of congestion and even accidents vehicles passing through the road. The number of movements on a road segment can be associated with the density of traffic flow on the road that is believed correlated with the speed of the vehicle and the volume of vehicles that occur per kilometers of roads. One of the problems that also exacerbate traffic conditions, is the problem of side friction on roads with heavy traffic flow. Obstacle Sideways is the impact on traffic performance from road segment side activities, including the lack of parking facilities in an area that will result in new parking activities, vehicles in and out of the side of the road, pedestrians and vehicles slow. The purpose of this research was to determine the effect of obstacles side and road performance. The results of the analysis carried out on the RTA road sections. km 9 use MKJI 1997 method obtained the highest traffic flow on Saturday of 867 smp/hour, the free flow speed of the vehicle is 41.21 km/hour, the side resistance weight of 493.8 with a class of medium / medium side barriers, the capacity of 2202 roads pcu/hour, the degree of saturation is 0.40 and the service level for the road (los) C is current speed is still stable, speed and movement are determined more by volume tall Keywords: Volume, Free Flow Speed, Side Barriers, Road Section Capacity, Service Level